Enhanced luminescence from silver nanoparticles integrated Er3+-doped boro-tellurite glasses: impact of annealing temperature - Said Mahraz, Zahra Ashur (Elsevier, 2015)
Considerable enhancement of rare earth ions luminescence intensity stimulated via metal nanoparticles (NPs) inclusion inside inorganic glass matrix opened a new avenue to achieving efficient lasing glass media. Tuning the localised surface plasmon resonance (LSPR) band of noble metal NPs through their precise size manipulation is demonstrated to be the key for such accomplishment. We report the influences of annealing (heat treatment) temperature (AT) on the down-conversion luminescence features of erbium (Er3+) doped zinc-boro-tellurite (ZBT) glasses containing silver NPs. The AT dependent (between 390 and 450 C) variations in refractive index and density are ascribed to the generation of non-bridging oxygen (NBO) ions. X-ray diffraction pattern confirmed the amorphous nature of the melt-quenched synthesized glass samples. TEM micrograph revealed the nucleation of Ag NPs inside the glass matrix having average diameter between 8.4 (un-annealed sample) to 11.8 nm (annealed). The UV-Vis spectra exhibited seven absorption bands corresponding to 4f-4f transitions of Er3+ ions. Annealed samples displayed a red shift of SPR bands positioned at 550 and 580 nm. Judd-Ofelt theory is used to evaluate the intensity parameters for radiative transitions within 4fn configuration of Er3+ ion. Annealing up to 410 C is found to stimulate the plasmonic effect through the enlargement of NPs. Consequently, the PL intensity is enhanced by a factor of 3.23 (2H11/2 ? 4I15/2), 4.10 (4S3/2 ? 4I15/2), and 3.79 (4F9/2 ? 4I15/2). This achieved excellent down-conversion luminescence efficiency of proposed glasses shows their potential implementation in photonic devices and solid state lasers.